2002
DOI: 10.1053/bbmt.2002.v8.pm12434950
|View full text |Cite
|
Sign up to set email alerts
|

Use of thrombopoietin in combination with chemotherapy and granulocyte colony-stimulating factor for peripheral blood progenitor cell mobilization

Abstract: This phase I/II dose-escalation study examined the safety and efficacy of recombinant human thrombopoietin (rhTPO) and granulocyte colony-stimulating factor (G-CSF) for postchemotherapy mobilization of peripheral blood progenitor cells (PBPCs) in patients with advanced breast cancer. Patients received cyclophosphamide, etoposide, and cisplatin (CVP) followed by G-CSF (6 microg/kg twice a day) and rhTPO (0.6, 1.2, 2.4, or 3.6 microg/kg as a single dose on day 5 or as 3 doses on days 5, 7, and 9 after chemothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Other agents have been used to increase mobilization of CD34 cells from normal individuals, either alone or in combination 15,16 . Stem cell factor (SCF) and G‐CSF when given together appear to result in higher yields of CD34 cells than G‐CSF alone 17 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other agents have been used to increase mobilization of CD34 cells from normal individuals, either alone or in combination 15,16 . Stem cell factor (SCF) and G‐CSF when given together appear to result in higher yields of CD34 cells than G‐CSF alone 17 .…”
Section: Resultsmentioning
confidence: 99%
“…Other agents have been used to increase mobilization of CD34 cells from normal individuals, either alone or in combination. 15,16 Stem cell factor (SCF) and G-CSF when given together appear to result in higher yields of CD34 cells than G-CSF alone. 17 The small but significant incidence of anaphylaxis associated with SCF administration makes this agent less attractive for clinical use.…”
Section: Resultsmentioning
confidence: 99%
“…27 When TPO was added to G-CSF and chemotherapy as a part of the mobilizing regimen in patients with breast cancer, enhanced mobilization of HSC was observed. 29 Murray et al 14 demonstrated that TPO alone can efficiently mobilize primitive hematopoietic progenitor and stem cells with long-term repopulating ability into peripheral blood. Our data showed that administration of TPO in mice resulted in the same level of WBC increase as seen following G-CSF treatment and higher WBC count than post Flt-3L injections.…”
Section: Discussionmentioning
confidence: 99%
“…Outras citocinas com capacidade de recrutamento de CPH da medula óssea para o sangue periférico têm sido reconhecidas (Gajewski et al, 2002 (Stiff et al, 2000). Dawson et al (2005) (Liles et al, 2003).…”
Section: Citocinasunclassified